Epidemiologia molecular das infecções por rotavírus G2 ao longo de 16 anos (1992 a 2008) na região amazônica, Brasil - OLIVEIRA, Alessilva do Socorro Lima de (Universidade Federal do Pará, 2013)
In Brazil it is estimated that rotavirus causes 3,352,053 episodes of diarrhea, 655 853 visits to emergency rooms, 92,453 hospitalizations and 850 deaths involving children under 5 years of age. Rotavirus belongs to the family Reoviridae, genus Rotavirus. The viral particle consists of three concentric layers of protein and the viral genome of 11 segments making up a double-stranded RNA. Currently, 23 G genotypes and 31 P genotypes. have been recognized. Among the G genotypes detected so far, G2 represents one of the most important and it is usually associated with the genotype P [4]. Over the past three years it has been observed on a continental scale the reemergence of genotype G2, throughout the years following the introduction of universal rotavirus vaccination, particularly in Brazil. This study aimed at the molecular characterization of samples of G2 strains obtained from children participating in several studies on rotavirus gastroenteritis in the Amazon region, Brazil, from 1992 to 2008. We selected 53 rotavirus G2 samples which were sequenced for VP4 and 38 samples for VP7. These samples were genotyped by RTPCR and its products being purified, quantified and sequenced. Samples were also subjected to electrophoresis of RNA segments. The obtained sequences of VP4 and VP7 genes were aligned and edited using the program Bioedit (v.6.05) and compared with other sequences registered in the RV gene bank using the BLAST program. The phylogenetic tree was made using the program Mega 2.1. Of the total 53 samples sequenced for the VP7 gene, phylogenetic analysis revealed two lineages (II and III) and three sublineages (IIa, IIc, IId) that circulated in different periods in the population. Samples of sub-lineages IIa and IIc showed mutation at amino acid position 96(Asp/Asn). This modification may result in a conformational change of epitopes recognized by neutralizing antibodies. The G2 strains that circulated in Belém were identical to those circulating in other states in the Amazon region which were included in the study. The VP[4] gene was sequenced in the region of VP8*, yielding 36 which-belonged to genotype P[4] and tree to P[6] we could identify two strains: P[4]-4, occurring during 1998-2000 and the P[4]-5 during 1993-1994 and 2006-2008 periods. Our findings sustain recent findings indicating a worldwide reemergence of G2 genotypes of variant IIc, which were established in the population in combination with genotype P[4]-5. In our study, the high homology among G2 strains in various states suggests that detected mutations have even surpassed geographical and temporal barriers.